Odpowiedź :
Odpowiedź:
a) 4x - 10 = 6
4x = 6 + 10
4x = 16
x = 4
b) 25 - 3x = -2
-3x = -2 -25
-3x = -27
x = 9
c) -8 -4x = -12
-4x = -12 + 8
-4x = -4
x = 1
d) 7x + 15 = 3x - 1
7x - 3x = -1 - 15
4x = -16
x = -4
e) 6 - 4x = -2x + 18
-4x + 2x = 18 - 6
-2x = 12
x = -6
f) 5 + 9x = 6x - 10
9x - 6x = -10 -5
3x = -15
x = -5
g) 8 - 2x = 5 - 3x
-2x + 3x = 5 - 8
x = -3
h) 15 + x = 3x - 3
x - 3x = -3 -15
-2x = -18
x = 9
i) 14 - x = 4x + 4
-x - 4x = 4 - 14
-5x = -10
x = 2
j) 20x + 8 = 3x - 9
20x - 3x = -9 - 8
17x = -17
x = -1